High diagnostic yield of gastrointestinal endoscopy in children with intestinal failure - Ching, Y. Avery (2008)
PURPOSE: Children with intestinal failure (IF) often have gastrointestinal (GI) symptoms, including bleeding, increased stool output, and feeding intolerance. The use of endoscopic assessment of these symptoms has not been previously reported. This report evaluates the diagnostic yield of GI endoscopy in the setting of IF. METHODS: After institutional review board approval, we reviewed the medical records (including endoscopy, pathology and microbiology data) of patients with IF who underwent GI endoscopies between September 1999 and March 2007. RESULTS: Twenty-seven patients underwent 61 GI endoscopies: 34 esophagogastroduodenoscopies, 17 colonoscopies, 7 flexible sigmoidoscopies, and 3 ileoscopies. Indications for endoscopy, which were not mutually exclusive, included chronic diarrhea (39%, n = 24), GI bleeding (36%, n = 22), suspected bacterial overgrowth (36%, n = 22), and suspected peptic disease (15%, n = 9). Based on gross endoscopic appearance, histopathology, or microbiology, 43 (70%) procedures yielded abnormalities. These included infectious (20%, n = 12), anatomical (18%, n = 11), peptic (15%, n = 9), allergic (15%, n = 9), and other (2%, n = 1) findings. Eleven (73%) of 15 duodenal cultures grew a spectrum of 17 bacterial species. Overall, 24 (89%) of 27 patients had gross endoscopic, histopathologic, or microbiologic abnormalities. CONCLUSIONS: In pediatric patients with IF, diagnostic upper and lower GI endoscopies yield high rates of abnormalities and can help guide clinical management.